REFORMAS AL REGIMEN PENAL PARA ESTABLECER EL ESTUDIO PSICOLOGICO DEL PROFESIONAL DE LA SALUD QUE OCASIONE UN HOMICIDIO ININTENCIONAL DEL PACIENTE - Chiriboga Curipoma, Johanna Paola (2016)
The Constitution of the Republic of Ecuador pursuant to Article 66 says that "recognize and guarantee to individuals: the right to the inviolability of life. There will be no death penalty; the right to a decent life that ensures health, food and nutrition, clean water, shelter, sanitation, education, labor, employment, rest and leisure, physical culture, dress, social security and other necessary social services; the right to personal integrity, which include physical, mental, moral and sexual integrity. The national health system aims development, protection and recovery capabilities and potentials for both healthy and integral life individually and collectively, and recognize the social and cultural diversity” Regarding the Organic Law of Health its first article states that "is to regulate the actions to effectuate the universal right to health enshrined in the Constitution of the Republic and the law" Organic Integral Penal Code article 146 says "The person to infringe an objective duty of care, in the exercise or practice of his profession, causes the death of another, shall be punished with imprisonment of one to three years. The qualification process to return to their work after completion of sentence will be determined by law. It shall be punished with imprisonment of three to five years if death occurs p9or unnecessary, dangerous and illegal actions. " 5 As we all know, the right to life is the main universal right enshrined and accepted in all constitutions, and we are all entitled to this and no one can be deprived of it arbitrarily. The right to life, in all its manifestations is a requirement of the rule of law, which criminalizes those who violate this. While the state has criminalized the conduct of involuntary manslaughter caused by a health professional, you do not have a psychological study for the professional who caused it, creating fear among health professionals, as exogenous factors not investigated that They led to commit this crime and are left completely defenseless, so that this would violate the rights enshrined in the Constitution, including the right to security we have all citizens. So before this, receive a criminal trial against him, it should assess the psychological status of the professional, to establish the reasons that come to commit this crime, since in many cases the stress to which they are involved makes them act negligently, another point would protect the identity of the doctor and the institution until it is declared guilty or innocent should never publish his identity, as this would preserve their honor.